Channel Crosstalk Impact on OCDMA Performance under Efficient Diagonal Code and Optimized Pulse Shaping - Atiya Y.S.; Abd H.J.; Salim N.; Din N.M.; Omran K. (Institute of Physics Publishing, 2023)
This paper examines the four-wave mixing (FWM) effect on optical code-division multiple-access (OCDMA) performance systems in the presence of Multi-Diagonal code (MD). System performance improvement is accomplished by means of fibre length tuning and stratified different modulation shapes, which are Non-return-to-Zero (NRZ), Gaussian, and Sine wave, all examined with 500 and 1Gb/s data rate values. The tests show that the NRZ modulation offers better system performance compared with other modulations for all data rate values used. Moreover, the second channel of each user offered better system performance than the other channels used. For instance, for 1Gb/s, at the second channel, the NRZ modulation offered the best performance with a quality factor (Q -factor) of 5.1 at 100 km fibre length, whereas the first channel introduced a worse Q-factor of 3.1 at the same fibre length value. Published under licence by IOP Publishing Ltd.